Pengaruh Laba Dan Arus Kas Terhadap Kondisi Kesulitan Keuangan Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Ardiansyah Japlani; Karnila Ali; Yenca Tasya Vara Renca (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study aims to examine and analyze the effect of earnings and cash flow on financial distress. The population in this study are food and beverage sector companies that are listed on the Indonesia Stock Exchange and continuously publish financial reports in 2018-2020. The sample of this study was determined by purposive sampling method in order to obtain 17 sample companies. This study uses secondary data obtained from the Indonesian capital market directory and www.idx.co.id. The analytical method used is the classical assumption and multiple regression analysis. The results of this study indicate that earnings and cash flow have a significant influence on the possibility of financial distress.